Educational outcomes for the Canadian workplace : new frameworks for policy and research - Gaskell, Jane S. (Jane Stobo); Rubenson, Kjell, 1944- (University of Toronto Press, 2004)
"Educational Outcomes for the Canadian Workplace explores how educational programs are changing, which skills matter in the economy, and how policy has responded to the educational and economic pressures of the 1990s. In this volume, Jane Gaskell and Kjell Rubenson have brought together a distinguished group of scholars from economics, commerce, sociology of education, adult education, and educational administration to discuss a broad range of issues related to education and the economy in Canada. The implications of their discussions are far-reaching: educational policy not only affects the development of skills and knowledge for a competitive labour market, but also has an impact on social equality, economic growth, and civic engagement. Presenting in-depth research and analysis, this volume makes a significant contribution to Canadian and international debate on the meaning of the new global economy for educational policy and practice."--Jacket